2011
DOI: 10.1121/1.3557033
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high-frequency energy changes in sustained vowels produced by singers

Abstract: The human voice spectrum above 5 kHz receives little attention. However, there are reasons to believe that this high-frequency energy (HFE) may play a role in perceived quality of voice in singing and speech. To fulfill this role, differences in HFE must first be detectable. To determine human ability to detect differences in HFE, the levels of the 8-and 16-kHz center-frequency octave bands were individually attenuated in sustained vowel sounds produced by singers and presented to listeners. Relatively small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 21 publications
2
39
1
Order By: Relevance
“…The draw has been due to sparse but increasingly conclusive evidence that high-frequency energy (HFE, defined here as the energy in the 8-and 16-kHz octave bands or 5.7-22 kHz) plays a larger perceptual role in speech perception than previously assumed. The percepts impacted by HFE that have been reported thus far are speech and voice quality (Olson, 1947;Moore and Tan, 2003;Moore et al, 2010;Monson et al, 2011), speech source localization (Best et al, 2005), speech intelligibility (Lippmann, 1996;Stelmachowicz et al, 2001;Apoux and Bacon, 2004;Moore et al, 2010), and child word-learning (Stelmachowicz et al, 2007;Pittman, 2008). Some studies indicate that HFE could also play a role in the perception of voice disorders (de Krom, 1995;Hartl et al, 2003) and in talker identification (Hayakawa and Itakura, 1995;White, 2001;Liss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The draw has been due to sparse but increasingly conclusive evidence that high-frequency energy (HFE, defined here as the energy in the 8-and 16-kHz octave bands or 5.7-22 kHz) plays a larger perceptual role in speech perception than previously assumed. The percepts impacted by HFE that have been reported thus far are speech and voice quality (Olson, 1947;Moore and Tan, 2003;Moore et al, 2010;Monson et al, 2011), speech source localization (Best et al, 2005), speech intelligibility (Lippmann, 1996;Stelmachowicz et al, 2001;Apoux and Bacon, 2004;Moore et al, 2010), and child word-learning (Stelmachowicz et al, 2007;Pittman, 2008). Some studies indicate that HFE could also play a role in the perception of voice disorders (de Krom, 1995;Hartl et al, 2003) and in talker identification (Hayakawa and Itakura, 1995;White, 2001;Liss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, the major contributors to HFE in running speech are consonants (Monson et al, 2011), and particularly voiceless fricatives (Jongman et al, 2000;Maniwa et al, 2009;Monson et al, 2012). Second, it has been suggested that HFE is of greater perceptual consequence for female talkers (Stelmachowicz et al, 2001), who tend to have higher HFE levels, at least in the 16-kHz octave (Monson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations